Perfectly undone [large type] - Raintree, Jamie (Wheeler Publishing, a part of Gale, a Cengage Company, 2018)
"Dr. Dylan Michels has worked hard for a perfect life, so when her longtime boyfriend, Cooper, gets down on one knee, it should be the most perfect moment of all. Then why does she say no? For years, Dylan's been living for her sister who never got the chance to grow up. Trying to be the perfect daughter, perfect partner and perfect doctor hasn't been enough to silence the haunting guilt Dylan feels over her sister's death--and the role no one knows she played in it. Dylan must face her past if she and Cooper stand a chance at a future together."--Back cover.